WHEAT AND SOYBEAN PRODUCTIVITY ON A DARK RED LATOSOL DUE TO DIFFERENT LEVELS OF SOIL EROSION UNDER NATURAL RAINFALL - Gaertner, Carlos; Dedecek, Renato Antonio; Biscaia, Rui Maranhão (Scientia Agraria, 2006)
Many data are available about soil losses by rainfall erosion, few data are available about the influence of these losses on soil productivity. This study was conducted in 1995, on soil erosion plots from Polo Regional IAPAR/Ponta Grossa-PR, which had been monitored for 17 years. Productivity of wheat (Triticum aestivum) and soybean (Glycine max), on soil erosion plots having different soil tillage systems was evaluated: no tillage, alternate (no tillage and minimum tillage), minimum tillage, conventional tillage and fallow plots at two different lengths (11 and 22 m). Wheat productivity was reduced due to soil losses by water erosion, as an average 116 kg.ha-1.cm-1, and soybean productivity was even more reduced, 139 kg.ha-1.cm-1 of soil lost. Wheat, especially on no tillage plot, was severely affected by the incidence of take-all disease (Geaumannomyces graminis), being difficult to establish any correlation between soil chemical and physical characteristics and productivity. Organic carbon content at soil layer 10 to 20 cm showed correlation with wheat and soybean yield, but correlation coefficient was less than 50%.